2015
DOI: 10.1007/s00277-015-2377-0
|View full text |Cite
|
Sign up to set email alerts
|

Mean corpuscular volume of control red blood cells determines the interpretation of eosin-5′-maleimide (EMA) test result in infants aged less than 6 months

Abstract: Eosin-5′-maleimide (EMA) binding test is a flow cytometric test used to detect hereditary spherocytosis (HS). To perform the test sample from patients, 5–6 reference samples of red blood are needed. Our aim was to investigate how the mean corpuscular volume (MCV) of red blood cells influences on the value of fluorescence of bounded EMA dye and how the choice of reference samples affects the test result. EMA test was performed in peripheral blood from 404 individuals, including 31 children suffering from HS. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…However, they did elaborate on different values coming from different instruments. Other studies using a similar metric have cited cutoffs of 81-85% (18,19). From our data, there appears to be a very good correlation between the measurement of the footprint and the MCF ratio/percentage, indicating that the footprint is a valid metric.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, they did elaborate on different values coming from different instruments. Other studies using a similar metric have cited cutoffs of 81-85% (18,19). From our data, there appears to be a very good correlation between the measurement of the footprint and the MCF ratio/percentage, indicating that the footprint is a valid metric.…”
Section: Discussionsupporting
confidence: 72%
“…However, the footprint data average was around 99.5% for each group, because the footprint was moved to fit the pattern of the normal and was generated using cord blood samples. Ciepela et al (18) also showed that mean fluorescence of EMA-bound RBC n/a 18.7 n/a n/a, not applicable. Foot print 5 analysis also included examination of a side scatter vs. EMA fluorescence plot also known as "footprint", location of the "footprint" is determined from a group of normal controls.…”
Section: Discussionmentioning
confidence: 98%
“…Eosin‐5’‐maleimide binding tests were performed as previously described . Briefly, 5 µL of whole blood from each sample was washed with saline and incubated in darkness at room temperature for 1 hour with 25 µL of EMA dye (0.5 mg/mL; Fluka, Gillingham, UK) with intermittent mixing.…”
Section: Methodsmentioning
confidence: 99%
“…It is more suitable to express EMA test results in percentage of fluorescence of control cells rather than mean fluorescence intensity, since different values of its intensity can be obtained using different flow cytometers or even samples of a dye prepared for staining. The cut‐off value for an EMA test to diagnose HS differs between laboratories and studied populations . Many studies do not include newborns to analyse EMA test specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, EMA was performed by using "MCV matched" controls to reduce the risk of lower sensitivity in neonates. 10 Patients were classified as severe HS (Hb <8 g/dL; n = 1), moderate HS (Hb 8-12 g/dL; n = 5) and mild HS (Hb >12 g/dL; n = 14). In the mild group, three patients were splenectomized.…”
Section: Evaluation Of a Hereditary Spherocytosis Screening Algorithmmentioning
confidence: 99%